2020
DOI: 10.3390/cancers12061669
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Recurrent Mutations and Clinically Meaningful Subgroups in Nodal Marginal Zone Lymphoma

Abstract: Nodal marginal zone lymphoma (NMZL) is a rare B-cell neoplasm, the genetic and transcriptomic landscape of which are unclear. Using high-throughput sequencing for whole-exome and transcriptome, we investigated the genetic characteristics of NMZL in a discovery cohort (n = 8) and validated their features in an extended cohort (n = 30). Novel mutations in NFKBIE and ITPR2 were found in 7.9% (3/38) and 13.9% (5/36), respectively, suggesting roles for the NF-κB pathway and B-cell-receptor-mediated calcium signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Fig. 5) [20,21,41]. A total of 34 samples sequenced by WES, accounting for 1593 variants, were included in the final list.…”
Section: Concordance Between Three Nmzl Wes Studiesmentioning
confidence: 99%
“…Fig. 5) [20,21,41]. A total of 34 samples sequenced by WES, accounting for 1593 variants, were included in the final list.…”
Section: Concordance Between Three Nmzl Wes Studiesmentioning
confidence: 99%
“…The present study revealed extensive genetic heterogeneity, there is a large number of genetic variations affecting many genes and pathways, re ecting the complexity of the HT process. Our results suggest that the genomic mutational landscape and CNA pro les of tMZL is much more complex than that of MZL [21,33,34]. We identi ed chromatin regulator genes were mutated in MZL (EP300) and tMZL (CREBBP and EP300), previous studies demonstrated that chromatin regulator genes mutations were early events in MZL [33,35].…”
Section: Discussionmentioning
confidence: 67%
“…Our results suggest that the genomic mutational landscape and CNA pro les of tMZL is much more complex than that of MZL [21,33,34]. We identi ed chromatin regulator genes were mutated in MZL (EP300) and tMZL (CREBBP and EP300), previous studies demonstrated that chromatin regulator genes mutations were early events in MZL [33,35]. Somatic mutations within regions of CNAs detected in our study, such as those in TNFAIP3, BCL10, and CD79B are associated with NF-κB activation and frequently mutated in de novo ABC-DLBCL [23,36].…”
Section: Discussionmentioning
confidence: 82%
“…The present study revealed extensive genetic heterogeneity, there is a large number of genetic variations affecting many genes and pathways, re ecting the complexity of the HT process. Our results suggest that the genomic mutational landscape and CNA pro les of tMZL is much more complex than that of MZL [21,33,34]. We identi ed chromatin regulator genes were mutated in MZL (EP300) and tMZL (CREBBP and EP300), previous studies demonstrated that chromatin regulator genes mutations were early events in MZL [33,35].…”
Section: Discussionmentioning
confidence: 72%
“…Our results suggest that the genomic mutational landscape and CNA pro les of tMZL is much more complex than that of MZL [21,33,34]. We identi ed chromatin regulator genes were mutated in MZL (EP300) and tMZL (CREBBP and EP300), previous studies demonstrated that chromatin regulator genes mutations were early events in MZL [33,35]. Somatic mutations within regions of CNAs detected in our study, such as those in TNFAIP3, BCL10, and CD79B are associated with NF-κB activation and frequently mutated in de novo ABC-DLBCL [23,36].…”
Section: Discussionmentioning
confidence: 99%